Cross cultural adaptation and psychometric properties of the Finnish version of Western Ontario shoulder instability index (WOSI) - Elamo Sami P.; Kukkonen Juha P.; Flinkkilä Tapio E.; Lehtinen Janne T.; Joukainen Antti K.; Paloneva Juha J.; Lehtimäki Kaisa K.; Kauko Tommi T.; Äärimaa Ville O. (BioMed Central Ltd, 2025)
Background: Western Ontario shoulder instability index (WOSI) is a widely used disease-specific self-assessment measurement tool for patients with shoulder instability. The main aim of this study was to translate and cross culturally adapt the WOSI into Finnish language and to test its measurement properties.
Methods: WOSI was translated in Finnish and adapted into an electronic user interface. 62 male patients with traumatic anteroinferior shoulder instability, programmed for stabilizing shoulder surgery, answered the questionnaire twice preoperatively (2 and 0 weeks), and twice postoperatively (3 and 12 months). Additional scoring tools, such as satisfaction to treatment outcome, subjective shoulder value (SSV), Oxford shoulder instability index (OSIS) and Constant score (CS), were used as comparators. The reliability, validity and responsiveness of WOSI were investigated through statistical analysis.
Results: Preoperative test-retest results were available for 49 patients, and 54 patients were available at final follow up. The mean WOSI was 57.8 (SD 20.3), 70.4 (SD 18.9), and 85.9 (SD 15.5), at baseline, 3, and 12 months, respectively. There was a statistically significant mean improvement of 28.8 (SD 24.5) in WOSI between baseline and 12 months (p < 0.0001). The intraclass correlation coefficient for the preoperative WOSI was excellent 0.91. At 12 months WOSI had an excellent Pearson's correlation coefficient both with SSV (0.69), OSIS (-0.81), and poor with CS (0.25) scores, confirming our a priori hypothesis. There were no detected floor nor ceiling effects for WOSI pre- or postoperatively. The calculated minimal detectable change was 9.2 and the estimated minimal clinically important difference 13.4 to 18.1.
Conclusion: Finnish version of WOSI is a reliable and valid tool for assessing health state and improvement after operative treatment of shoulder instability in young male patients.